Pengaruh Zakat, Infak, dan Sedekah terhadap Pertumbuhan Ekonomi Indonesia - Dewi Purwanti (Jurnal Ilmiah Ekonomi Islam, 2020)
Zakat is obligatory for all Muslims while infaq and alms are sunah. Zakat, infaq, and alms (ZIS) make distribution of wealth from the rich to the poor people. If the poor people are able to fulfill their basic needs, they can work well and contribute positively to the economy in various sectors. Zakat, infaq, and alms are expected to be one of the alternative policies to increase economic growth. However, to find out whether zakat, infaq, and alms have succeeded in positively contribute to economic growth, research is needed to prove the existence of the influence of zakat, infaq and alms in Indonesia. The purpose of this study is to determine the effect of zakat, infaq, and alms on the economy. This study uses a panel regression analysis with driscoll and kraay standars errors. The results of this study showed that zakat, infaq, and alms have positive effect on Indonesia's economic growth.